A Maqasid-Based Governance Framework for Islamic Banking: Integrating VBI, ESG, and Ethical Digital Transformation - Suardi, Didi; Azwar, Martavevi; Simatupang, Aisyah Defy R.; Septi, Iti; Komariyah, Oom; Tidjani, Shofiah (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2025)
This research contributes to the literature through the propositions of the Maqasid-Based Governance Framework (MBGF), which would help realign Islamic banking for sustainability and the digital era with higher objectives of Shariah. Drawing on the classical teachings of Al-Ghazali and al-Shatibi on maqasid al-shariah, and on modern governance views offered by Chapra, this study integrates maqasid al-shariah with VBI, ESG practices, and ethical digital governance. Based on a qualitative concept methodology, the paper synthesises ethical foundations, institutional governance, sustainability indicators, and digital innovation into a comprehensive governance architecture. The results indicate that the MBGF facilitates transparency, social value addition, eco-friendliness, and digital ethics in Islamic banking. The paper also highlights related indicators , such as the Maqasid Performance Index (MPI) and the Maqasid Shariah Index (MSI), to operationalise maqasid-based governance. The contribution of this paper is theoretical, in terms of giving a new positioning to maqasid as the broad governance framework; conceptual, in terms of amalgamating VBI, ESG, and digital ethics into a multi-layered model; and empirical, by providing regulators and practitioners with a practical governance blueprint for value-driven and sustainable Islamic finance.